Exploring electrolyte imbalances in cataractogenesis: A comparative analysis of sodium and potassium levels in diabetic and non-diabetic patients - Beatrice Choppara; Irigu Vijay Kumar; Aradhana Badam; Sara Sultana (Asian Journal of Medical Sciences, 2024)
Background: Cataract, a major cause of treatable blindness accounting for 80% of cases, arises from a complex etiology involving various factors. Diabetes notably expedites cataract development, and its potential interaction with electrolyte imbalances further enhances our understanding. Aims and Objectives: This study aimed to explore the concentrations of electrolytes, specifically sodium (Na⁺) and potassium (K⁺), in both serum and aqueous humor, and their potential implications in the pathogenesis of cataracts among individuals with diabetes. Materials and Methods: A comprehensive observational study encompassed a cohort of 100 cases, equally divided into diabetic and non-diabetic cataract patients. Gender distribution and age groups were established, focusing on individuals aged 40 years and above. Serum sodium (Na⁺) and potassium (K⁺) levels were compared against reference ranges, and statistical analyses included an unpaired Student’s t-test and the Statistical Package for the Social Sciences 20 software. Results: Among diabetic cataract patients, serum sodium levels were notably elevated (149.2147±2.71 meq/L) compared to non-diabetic counterparts (145.04±2.25 meq/L), demonstrating high significance (P<0.001). Similarly, diabetic patients exhibited a marginal increase in serum potassium (4.1919±0.5011) in contrast to non-diabetic patients (4.1264±0.5124), with a non-significant P-value (P<0.5). Aqueous humor analysis revealed a substantial rise in both sodium and potassium levels among diabetic cataract cases, demonstrating high significance (P<0.001). Conclusion: This study presents compelling evidence of distinct electrolyte profiles, particularly sodium and potassium, between diabetic and non-diabetic cataract patients. Elevated serum and aqueous humor sodium levels in diabetics suggest a potential contributory role in cataractogenesis.